Quantitative Determination of Myricetin in Rat Plasma by Ultra Performance Liquid Chromatography Tandem Mass Spectrometry and its Absolute Bioavailability - Dang, Y.; Lin, G.; Xie, Y.; Duan, J.; Ma, P.; Li, G.; Ji, G. (Drug Research, 2014)
Myricetin is a widely distributed bioactive flavonoid with scientific interest attributed to its anti-oxidant, antitumor, and anti-inflammatory properties. A specific and sensitive ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for identification and quantification of myricetin in rat plasma after oral and intravenous administrations. Kaempferol was used as an internal standard. Followed by β-glucuronidase and sulfatase hydrolysis and liquid-liquid extraction with ethyl acetate, the analytes were separated on an Acquity UPLC BEH C18 column (2.1×50 mm, 1.7 μm) and analyzed in the selected ion recording with a negative electrospray ionization mode. The developed method was validated for selectivity, accuracy, precision, linearity, recovery, stability and matrix effect. The assay was validated over a wide concentration range of 2–4 000 ng/mL. Intra- and inter-day precisions were all less than 13.49% and accuracy ranged from 95.75 to 109.80%. The present method was successfully applied to investigate a pharmacokinetic study of myricetin following intravenous and oral administrations to rats. The absolute bioavailability was found to be 9.62% and 9.74% at 2 oral doses (50 mg/kg and 100 mg/kg, respectively), which indicated myricetin was poorly absorbed after oral administration. To our knowledge, this is the first pharmacokinetic evaluation of myricetin as a single active pharmaceutical ingredient in preclinical studies.
Keywords: UPLC-MS/MS; myricetin; rat plasma; pharmacokinetics; absolute bioavailability